Caracterização geofísica e petrofísica dos turbiditos oligo-miocênicos do Campo de Marlim - Bacia de Campos - Brasil: análise de perfis sísmicos e de poço - Pelisam, Luís Gustavo Trettel [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The focus of the present work is the geophysical and petrophysical characterization of the main oligo-miocene turbidite of the Marlim Field, located in the northeast portion of the Campos Basin. The turbidite belongs to the Carapebus Formation and it is constituted by sandstone with low argilosity and high porosity, that forms the main reservoir rock of post-salt zone in this oil field. The Marlim Field is considered one of the giant oil fields in Brazil, however, since 2002, its production has decreased substantially, which highlights the necessity of new regional analysis in a reexploratory view of the mature Brazilian fields. In this context, the present work aims the tectono-stratigraphic characterization of the Oligo-Miocene turbidite of the Marlim Field, which includes the analysis and correlation of 16 wells, 11 2D seismic lines (578 km) and a 3D seismic cube (area equal to 30 km²), regularly distributed throughout the study area. The correlation sections allowed to identify the top and base of the turbidite as well as their variation of thickness along the field. The petrophysical maps based on resistivity, gamma ray and neutron porosity logs allowed to identify ideal areas to establish good hydrocarbon reservoirs. The seismic interpretation, the structural contour map and the isopach map were used to understand the oligo-miocene turbidite distribution in Marlim Field and adjacent areas, as well as to analyze the main faults systems and oil traps. This study helped in the tectono-stratigraphic understanding of the reservoir. It was observed that the NW portion of the Marlim Field represents the feeding turbidites zones, where are the most representative thicknesses, gradually decreasing towards SE, according to the natural platform bathymetric decreasing. The central and northeast portions of the Marlim Field are more prone to form good hydrocarbon reservoirs, which are mainly limited by normal faults that acted as oil migration routes...

O objeto de estudo do presente trabalho consiste na caracterização geofísica e petrofísica do principal corpo turbidítico de idade oligo-miocênica do Campo de Marlim, localizado na porção nordeste da Bacia de Campos. O turbidito pertence à Formação Carapebus, constituída por arenitos com baixa argilosidade e elevada porosidade, que classificam a unidade como a principal rocha reservatório da seção pós-sal deste campo. Marlim é considerado um dos campos gigantes de hidrocarbonetos do Brasil, no entanto, a partir de 2002, sua produção decaiu substancialmente, fato que realça a necessidade das análises regionais de cunho reexploratório sobre os campos maduros brasileiros. Neste contexto, o presente trabalho visa a caracterização tectono-estratigráfica do turbidito oligo-miocênico do Campo de Marlim, por meio da análise de 16 poços, 11 linhas sísmicas 2D, que totalizam 578 km e um cubo sísmico 3D de área igual a 30 km², todos distribuídos homogeneamente ao longo da área de estudo. As seções de correlação de poços estabelecidas possibilitaram identificar o topo e a base do turbidito de interesse, bem como sua variação de espessura ao longo do campo. Os mapas petrofísicos baseados em dados médios de perfis de resistividade, raio gama e porosidade neutrão permitiram identificar áreas com maior probabilidade de formar bons reservatórios de hidrocarbonetos. A interpretação sísmica e os mapas de contorno estrutural e isópacas foram utilizados para compreender como os turbiditos oligo-miocênicos se comportam estratigráfica e estruturalmente no Campo de Marlim e áreas adjacentes, bem como analisar os principais sistemas de falhas e trapas. Tal estudo facilitou o entendimento tectono-estratigráfico do reservatório. Constatou-se que os turbiditos possuem maiores espessuras em sua zona de alimentação a NW, reduzindo gradativamente em direção a SE, conforme os lobos seguem o mergulho normal da plataforma...
Keywords: Geologia estratigráfica; Turbidito; Geofisica; Poços de petroleo; Hidrocarbonetos; Petróleo; Campos, Bacia de (RJ); Brasil